Analysis of fillings in masonry – Case estudy: UEMG – Unit of João Monlevade (Research, Society and Development, 2019)
This article aims to present a survey of ceramic masonry walls pathological problems in the Universidade do Estado de Minas Gerais (UEMG), João Monlevade city. Aperture, shape, location and activity are the characteristics used to classify fissures. Several factors can lead to the appearance of them. Knowledge related to this topic is presented in this article. Literature review of the concept and intrinsic and extrinsic causes of construction pathology and fissures in masonry were done. A field survey with photography records were carried out in the studied buildings. The data were collected, analyzed and quantified. Fissures caused by stress concentration in window corners, retraction fissures, fissures caused by dilatation and contraction in the masonry and the structural element junction, fissures caused by floor system overload, fissures caused by thermal movement and fissures cause by hygroscopic movement were surveyed. As result, the causes were identified and corrective management were proposed for each fissure surveyed.